2005
DOI: 10.1021/jm0491849
|View full text |Cite
|
Sign up to set email alerts
|

CoMFA, Synthesis, and Pharmacological Evaluation of (E)-3-(2-Carboxy-2-arylvinyl)-4,6-dichloro-1H-indole-2-carboxylic Acids:  3-[2-(3-Aminophenyl)-2-carboxyvinyl]-4,6-dichloro-1H-indole-2-carboxylic Acid, a Potent Selective Glycine-Site NMDA Receptor Antagonist

Abstract: (E)-3-(2-Carboxy-2-phenylvinyl)-4,6-dichloro-1H-indole-2-carboxylic acid, 1, is a potent and selective antagonist of the glycine site of the N-methyl-d-aspartate (NMDA) receptor. Using 3D comparative molecular field analysis (CoMFA) to guide the synthetic effort, a series of aryl diacid analogues of 1 were synthesized to optimize in vivo potency, duration of action, and binding activity. It was found that the incorporation of a substituted aromatic with an electron withdrawing group or a heterocyclic group at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…We came across some studies involving 3D-CoMFA (Comparative Molecular Field analysis) methodology [32,33,34,35,36]. Although quite routinely reported; observations from such studies are difficult to compare with already established QSAR studies.…”
Section: Resultsmentioning
confidence: 99%
“…We came across some studies involving 3D-CoMFA (Comparative Molecular Field analysis) methodology [32,33,34,35,36]. Although quite routinely reported; observations from such studies are difficult to compare with already established QSAR studies.…”
Section: Resultsmentioning
confidence: 99%
“…Such information will be helpful in identifying new classes of glycine antagonists such as subtype selective antagonists. Still challenges for the development of NMDA-glycine antagonists are present [85][86][87][88][89][90].…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis of speradine C by Liu et al 42 In 2005, Baron and coworkers utilized the dehydration of -hydroxytryptophan-like species to prepare a library of selective glycine-site N-methyl-D-aspartate (NMDA) receptor antagonists. 43 The researchers found that diastereomeric mixtures of -hydroxy-and -trimethyl silyl (TMS) ether compounds 1.41a-b could be converted to the corresponding dehydrotryptophan-like species 1.42 upon the addition of either para-toluenesulfonic acid (pTsOH) or trifluoromethanesulfonic anhydride (Tf2O) in high yields (Scheme 1.18). Baron and coworkers also found that, in one scenario, attempted dehydration of an intermediate TMS ether resulted in a quantitative retro-aldol reaction when trifluoracetic acid (TFA) was used as the source of acid.…”
Section: Dehydrotryptophan Derivatives By Acid-catalyzed Elimination Of Water Fromhydroxytryptophanmentioning
confidence: 99%